2020
DOI: 10.1002/hsr2.151
|View full text |Cite
|
Sign up to set email alerts
|

Elbasvir and grazoprevir for hepatitis C virus genotype 1 infection in people with recent injecting drug use (DARLO‐C): An open‐label, single‐arm, phase 4, multicentre trial

Abstract: Background and AimsDirect‐acting antiviral therapy for hepatitis C virus (HCV) is effective, but few prospective studies among people with ongoing injecting drug use exist. This study evaluated the efficacy of elbasvir/grazoprevir in people with HCV genotype 1/4 (G1/4) infection and recent injecting drug use. An exploratory aim evaluated the feasibility of fingerstick point‐of‐care HCV RNA testing prior to and following treatment.MethodsDARLO‐C (ClinicalTrials.gov: NCT02940691) is an open‐label phase 4 trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The Xpert HCV Viral Load Fingerstick assay and the Xpert HCV Viral Load assay (Cepheid, Sunnyvale, California) both enable diagnosis of active infection by detecting HCV RNA in 1 hour and have a pooled sensitivity and specificity of 98% and 100%, respectively. The test has been used in multiple research and programmatic studies globally [ 31 ], including in Australia [ 33–36 ], Tanzania [ 37 ], Spain [ 38 ], Italy [ 39 ], Switzerland [ 40 ], France [ 41 ], Indonesia [ 42 ], and Cambodia [ 43 ]. Although the Cepheid platform is already used in the US for the diagnosis of other infections [ 44 ], this test is not yet FDA approved.…”
Section: What Is Workingmentioning
confidence: 99%
“…The Xpert HCV Viral Load Fingerstick assay and the Xpert HCV Viral Load assay (Cepheid, Sunnyvale, California) both enable diagnosis of active infection by detecting HCV RNA in 1 hour and have a pooled sensitivity and specificity of 98% and 100%, respectively. The test has been used in multiple research and programmatic studies globally [ 31 ], including in Australia [ 33–36 ], Tanzania [ 37 ], Spain [ 38 ], Italy [ 39 ], Switzerland [ 40 ], France [ 41 ], Indonesia [ 42 ], and Cambodia [ 43 ]. Although the Cepheid platform is already used in the US for the diagnosis of other infections [ 44 ], this test is not yet FDA approved.…”
Section: What Is Workingmentioning
confidence: 99%
“…20 Studies largely from Australia and Europe reported that people who use drugs infected with HCV can be effectively screened, treated and cured with direct-acting antivirals (DAAs). [21][22][23] In fact, to meet the 2030 HCV elimination goals set forth by WHO, it was suggested that people who use drugs be specifically engaged for treatment to reduce the potential for HCV transmission. 24,25 Treating people who inject drugs makes sense from a public health perspective; if an active person who injects drugs is cured, they will no longer transmit the virus through sharing of infected syringes or other injection paraphernalia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies largely from Australia and Europe reported that people who use drugs infected with HCV can be effectively screened, treated and cured with direct‐acting antivirals (DAAs) 21–23 . In fact, to meet the 2030 HCV elimination goals set forth by WHO, it was suggested that people who use drugs be specifically engaged for treatment to reduce the potential for HCV transmission 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“… 4 - 6 Despite concerns about reinfection risk and nonadherence to HCV treatment, there is some evidence that HCV treatment is effective in this population. 1 , 7 - 10 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Despite concerns about reinfection risk and nonadherence to HCV treatment, there is some evidence that HCV treatment is effective in this population. 1,[7][8][9][10] HCV infection is typically diagnosed and assessed in several sequential steps, including antibody (anti-HCV) testing followed by confirmation of the presence of an active infection (HCV RNA), determination of the HCV genotype, and evaluation of liver fibrosis. This approach requires multiple visits, and there is a risk of attrition in between visits.…”
Section: Introductionmentioning
confidence: 99%